“Does Brexit mean Brexit?” “Ave, Brussels, brexituri te salutant” (Comillas Journal of International Relations, 2021)
A large majority of EU citizens show a great lack of interest about the issues that concern it. In fact, institutions such as the ECSC, the EEC, the EURATOM or treaties such as Maastricht, Amsterdam, Nice or Lisbon are rarely topics of conversation among them. Only the withdrawal process of United Kingdom from the EU raises some concern among EU citizens, because the perceived influence it will have on our economies. They speak of Brexit, of the “withdrawal agreement”, of “backstop”, etc., but without getting to the heart of these concepts. Since its creation, the EU has not stopped moving forward in the construction of its integration project. The British governments do not seem to have fully identified with the ultimate goal of the process: the political union. Thus, based on a short account of the European project, we will study the Brexit event, analyzing what these four years have meant, both for the EU and for the UK, until the arrival of “hurricane Johnson” with his controversial and disputed decisions.
Keywords: withdrawal agreement; backstop; Boris Johnson; Brexit; brexiteers; political declaration; Jeremy Corbyn; Westminster Parliament; 2016 Referendum; United Kingdom; remainers; Theresa May; European Union